Experimental and simulation study on the impact resistance of concrete to replace high amounts of fine aggregate with plastic waste. (December 2022) - Al-Tayeb, Mustafa Maher; Aisheh, Yazan I. Abu; Qaidi, Shaker M.A.; Tayeh, Bassam A.
Abstract: The impact of substantial amounts of plastic waste (PW) substituted fine aggregate (FA) on the mechanical characteristics of concrete under impact load (I.L) was studied experimentally-and-numerically. As fine aggregate substitutes, samples were made with 0%, 20%, 30%, and 40% PW. Six prisms of 100 mm width, 50 mm depth, and 400 mm length were loaded to failure in a drop-weight impact machine after 28 days by exposing them to 30 N of weight from a 400 mm height, while another three prisms of the same size and age were evaluated under static load(S.L). The load-displacement(L-D) and fracture energy(GF ) of normal and concrete with PW prisms under S.L and I.L were investigated. A 3D finite element technique simulation was also carried out using LUSAS V.14 to investigate the impact of L-D behavior, and the predictions were confirmed by experimental findings. Despite reducing the fine aggregate amount, it was discovered that a proportionate increase of PW up to 20% can lead to improvements in bending load, impact tup, and inertial load.